Creating A New Development Path on The Example of the Łódź Special Economic Zone - Waldemar JAGODZIŃSKI; Ireneusz MICIUŁA; Henryk WOJTASZEK (Communications of International Proceedings, 2020)
In this article a new development path was created on the example of the Łódź Special Economic Zone. The main research effort in this case is focused on finding an event that gives a particular phenomenon a "cause and effect sequence with deterministic properties. This event is not without cause, but one that contradicts the predicted results resulting from the explanatory model used. It may therefore be an individual decision, but it may also be a random, large-scale phenomenon. Such an event may, for example, be the creation of a special economic zone in a given region. The analysis of a number of activities undertaken by the Łódź Special Economic Zone leads to the conclusion that the process of creating a new path assumes that the economy will diversify into technologically related industries. This process is in partial opposition to the six rules of industrialization reflected in the development of industrial cities.  In an innovative economy, standardization is being replaced by uniqueness and creativity, with soft skills taking the place of specialization, and therefore social capital is becoming increasingly important to respond quickly to changes in the environment.
Keywords: Economy; New Development Path; Łódź Special Economic Zone; Innovation; Entrepreneurship; Business Law.